PERTUMBUHAN DAN HASIL TANAMAN JAGUNG GENOTIPE F14 DI LAHAN GAMBUT - IRWANDO, SISCO LASBUAN (Fakultas Pertanian Universitas Tanjungpura, 2019)
This study aims to examine at the growth and yield of genotypes corn F14 on peat soil. This research was carried out in peat soil area in Rasau Jaya II from 24 January 2 June 2018. The study used a randomized complate block design (RCBD) consisting of five F14 genotypes ( B, C, D, E and F) maize as a treatment and one comperative variety which is Arjuna variety (A), each treatment is made into five groups and six replications. The results showed that F14 genotypes that had good growth were genotypes A, B, C and genotypes that had good results were genotypes D and E.Keywords : growth, maize, peat, results